Registry of the Egyptian specialized hypertension clinics: Sex‐related differences in clinical characteristics and hypertension management among low socioeconomic hypertensive patients - Amr Abdel Aal; Ghada Youssef; Amr El Faramawy; Dalia El Remisy; Heba El Deeb; Wafaa El Aroussy; M. Mohsen Ibrahim (The Journal of Clinical Hypertension, 2021)
Abstract Hypertension is a major modifiable risk factor for cardiovascular disease (CVD) which is a leading cause of death in developing countries affecting both genders. Gender dissimilarity in clinical characteristics and hypertension (HTN) management among hypertensive patients has been reported in several reports before. The aim was to detect sex differences in clinical characteristics and HTN management among Egyptian hypertensive patients. Data from 4701 hypertensive patients attending 9 university located Specialized Hypertension clinic (SHC) were collected from October 2014 to September 2017. The collected data included demographics, cardiovascular risk profile, hypertension‐related history, anthropometric and blood pressure (BP) measurements, antihypertensive medications used, number of patients attending the follow‐up visits, and HTN control rate. Females represented 58.5% of the recruited patients, they were younger, with higher BMI, lower education level, and employment rate compared with males. Females had lower mean office systolic and diastolic BP than males (144.2 ± 22.6 vs. 146.5 ± 22.0 mmHg and 88.1 ± 13.0 vs. 89.9 ± 12.6 mmHg, respectively) and lower rate of uncontrolled BP (54.8% vs. 61.1% in males P < .001). Antihypertensive drugs were comparable among both sexes except for angiotensin converting enzyme inhibitors which were more prescribed in males. Compliance to antihypertensive medications was better in females (63.6% vs. 60.1% in males, P = .015). To conclude, Egyptian hypertensive females have different clinical characteristics as compared to their counterpart males with better BP control, adherence to antihypertensive medications, lower systolic and diastolic BP, and no major differences in the prescribed antihypertensive distribution.